HPTLC determination of diosgenin in fenugreek seeds - Król-Kogus Barbara; Lamine Khenifi Mohammed; Migas Piotr; Boudjeniba Messaoud; Krauze-Baranowska Mirosława (Acta Pharmaceutica)
A new HPTLC-densitometric method for diosgenin determination in fenugreek seeds was established after optimization of the conditions for efficient saponin extraction and acid hydrolysis. Several procedures were tested, the best of which was a three-step Soxhlet extraction, followed by hydrolysis of the obtained methanolic extract with 2 mol L-1 H2SO4. Best diosgenin separation from other hydrolysis products was obtained on HPTLC Si60F254 plates u sing a mixture of n-heptane/ethyl acetate (7:3, V/V) and modified anisaldehyde as a spraying reagent. The method was preliminarily validated and the determined amounts of diosgenin in fenugreek seeds of Polish and African origin were found to be similar and ranged from 0.12-0.18 %.